0789 Sleepwalking and Sleeptalking in Children: Associations with Emotional/Behavioral Problems and Sleep Quality. (27th April 2018) - Laganière, C; Gaudreau, H; Pokhvisneva, I; Atkinson, L; Meaney, M; Pennestri, M
Abstract: Introduction: Sleepwalking (SW) is a parasomnia involving unusual and complex behaviors initiated during sleep, such as walking, sitting or eating. It has been proposed that sleeptalking (ST) shares similar underlying mechanism with SW. A few studies found associations between these parasomnias and: separation anxiety, hyperactivity-inattention symptoms, as well as environmental factor such as parental divorce. However, the association between ST-SW and psychological symptoms assessed with validated measures in childhood remains to clarify. The aim of this project is to compare emotional/behavioral problems, as well as sleep patterns, in children with and without SW/ST. Methods: This project is part of the study, Maternal Adversity Vulnerability and Neurodevelopment (MAVAN)(n=277). Presence of SW, ST, sleep duration, number and duration of night awakenings were assessed with the Children Sleep Habits Questionnaire, and Emotional/behavioral problems were assessed with the Child Behavior Checklist (CBCL) at 4 and 5 years old. Independent sample T-tests were used to assess differences between children with and without SW/ST. Results: At 4 years old, 2.7% of children presented SW and 27.4% ST. At 5 years old, 4.4% of children were sleepwalking and 20.5% sleeptalking. Five-year-old children with SW or ST (or both), had more depressive problems (2.68 ± 2.41 vs 1.67 ± 1.81, p=.001), anxiety problems (9.984 ± 3.36 vs 2.16±=2.18, p<.001), pervasive developmental problems (3.84 ± 2.67 vs 2.68 ± 2.41, p=.001), and oppositional/defiant problems (3.33 ± 2.49 vs 2.60 ± 2.53, p=.04) than children without SW/ST. Similar results were observed at 4 years old. Although children with SW or ST (or both) had more night awakenings (4.45 ± 1.53 vs 3.92 ± 1.36, p=.01) than children without SW/ST, no differences were found in sleep duration and duration of awakenings (p>.05). Conclusion: Children who experienced SW and∕or ST also had more depressive, anxious, pervasive developmental and oppositional/defiant problems than children without SW/ST. While they also showed more nocturnal awakenings, other sleep characteristics were not affected. A better understanding of the mechanisms linking parasomnias and psychological problems could eventually represent a new therapeutic avenue to the treatment of both psychological and sleep problems. Support (If Any): Canadian Institute of Health Research, Ludmer Centre for Neuroinformatics and Mental Health.